The Importance of Role-Playing in Promoting Motivation and Oral Communication among Non-Arabic Speakers: Language Acquisition - Abdelhafid, Karima Aboubaker; Mustapha, Nik Farhan; Ismail, Muhd Zulkifli; Hassan, Abd Rauf (Al-Ḍād Journal, 2024)
Abstract Motivation has an important role in learning a foreign language. Without it, the process of learning the language will be more difficult, and students may lose motivation and stop learning the language, on the other hand, oral communication is a great challenge, especially when they learn that language in their country, far from the original environment of the language. In this regard, studies have indicated that role-playing activities play a major role in stimulating motivation and developing oral communication among students in learning foreign languages. Therefore, this study aimed to reveal the level of motivation and oral communication among non-Arabic speaking learners after learning this language through role-playing activities. To achieve the aim of the study, the quasi-experimental approach with a single group design was used. The study included 40 Malay male and female students who specialize in the Arabic language at a public university in Malaysia. An applied model of role-playing activities taken from daily life was conducted in the classroom, and to measure the level of oral communication an oral test was used before and after the experiment. Results showed that students’ motivation was good before and after the activities, indicating satisfactory motivation levels. Additionally, the level of oral communication was significantly improved, ranging from very good to excellent after the experiment. The study also confirmed that including role play as a linguistic activity increases interaction and teamwork between students and teachers, enhances students’ self-confidence, and enables them to express their feelings. Keywords: Role-playing activities, motivation, oral communication